Applications of continuous renal replacement therapy for hepatic encephalopathy - Jiao Jing; Wei Sui-jiao; Bai Ming; Zhang Peng (Linchuang shenzangbing zazhi)
Continuous renal replacement therapy （CRRT）， also known as continuous blood purification （CBP）， is capable of quickly removing blood toxins and improving metabolic disorders. It has become a vital treatment for critically ill patients. As a serious neuropsychiatric complication of liver insufficiency and portosystemic shunt， hepatic encephalopathy （HE） is associated with a high mortality and a poor prognosis. Disorder of ammonia metabolism is a core pathogenesis of HE. CRRT is effective in boosting blood ammonia clearance， improving inflammatory status， alleviating cerebral edema and balancing internal environment. This review summarized the relevant therapeutic mechanism of CRRT to provide useful guidance for routine practices and clinical trials.